European encounters with the New World : from Renaissance to Romanticism - Pagden, Anthony (Yale University Press, 1993)
For review see: J.W. Schulte Nordholt, in Tijdschrift voor geschiedenis, jrg. 107, nr. 4 (1994); p. 591-592.